Efektivitas Penerimaan Pajak Bumi dan Bangunan Pada Badan Pendapatan Asli Daerah Kabupaten Gowa - Nurfadilah, Nurfadilah; Parawu, Hafiz Elfiansya; Rasdiana, Rasdiana (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
This study aims to determine the effectiveness of land and building tax revenues at the Gowa Regency Original Revenue Agency. This type of research is descriptive qualitative. Data collection techniques were carried out by using observation, interviews, and documentation techniques with a total of 5 informants. Data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions. The results showed that in 18 sub-districts of Gowa Regency it was not yet effective. The reason is the lack of public awareness in paying taxes. Taxpayers pay PBB only if there is a need, such as selling the land because there must be a PBB payment report or there are other government arrangements and in the application of the tax many SPPT are considered problematic and in the application of the tax there are many SPPT which are considered problematic. Among them, the subject does not exist, the object is unclear or in a state of dispute or multiple PBB so that they return it to the BAPENDA office.